The genome sequence of a cranefly, Tipula lateralis Meigen, 1804 [version 1; peer review: 2 approved] - Olga Sivell; Duncan Sivell (Wellcome Open Research)
We present a genome assembly from a female specimen of Tipula lateralis (cranefly; Arthropoda; Insecta; Diptera; Tipulidae). The genome sequence has a total length of 701.32 megabases. Most of the assembly (89.15%) is scaffolded into 4 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 16.5 kilobases. Gene annotation of this assembly on Ensembl identified 11,388 protein-coding genes.